2006
DOI: 10.1177/001440290607200404
|View full text |Cite
|
Sign up to set email alerts
|

The Chronic and Increasing Shortage of Fully Certified Teachers in Special and General Education

Abstract: This study addresses the chronic and increasing national shortage of fully certified special education teachers (SETs) in comparison with general education teachers (GETs). The data sources were the 1987-1988 through 1999-2000 Schools and Staffing Surveys and the Data Analysis System for special education for school years 1987-1988 through 2001-2002. The study found that (a) the shortage of fully certified SETs increased from 7.4% in 1993-1994 to 12.2% in 2001-2002 (2%-4% greater than the shortage of fully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 10 publications
1
82
1
Order By: Relevance
“…Given that extensive teacher preparation is designed to produce graduates who will satisfy full certification requirements set by states (NASDTEC, 2003), it might seem surprising that substantially less than 100% of beginning SETs and GETs were not fully certified. This is to be expected, however, because our definition is "fully-certified in a teacher's main teaching assignment," whereas many teachers are fully certified, but in some other teaching assignment (Boe & Cook, 2006). Similarly, a large percentage of teachers are given a main teaching assignment that is out of the field of their degree major (see results in Table 1 for the teaching assignment variable).…”
Section: Do Teacher Qualifications Vary By Amount Of Teacher Preparatmentioning
confidence: 92%
“…Given that extensive teacher preparation is designed to produce graduates who will satisfy full certification requirements set by states (NASDTEC, 2003), it might seem surprising that substantially less than 100% of beginning SETs and GETs were not fully certified. This is to be expected, however, because our definition is "fully-certified in a teacher's main teaching assignment," whereas many teachers are fully certified, but in some other teaching assignment (Boe & Cook, 2006). Similarly, a large percentage of teachers are given a main teaching assignment that is out of the field of their degree major (see results in Table 1 for the teaching assignment variable).…”
Section: Do Teacher Qualifications Vary By Amount Of Teacher Preparatmentioning
confidence: 92%
“…This model is sometimes practiced with the help of a clinical experiences staff person and sometimes not (Prater & Sileo, 2002, 2004. Since most schools employ only a few special education teachers at best and perhaps as many as half of those are either novices in their first few years of teaching or out-offield aspiring special educators (e.g., Boe & Cook, 2006), it can be very difficult to find enough quality field sites to meet every student's needs (Epanchin & Colucci, 2002;Jenkins et al, 2002). Moreover, research on teacher attrition in special education has consistently shown that the number of teaching vacancies that occur each year far outstrips the number of newly qualified graduates prepared to occupy those positions and that many of those who leave their classrooms each year are seasoned veterans (McLeskey & Billingsley, 2008).…”
Section: The Challenges To Community Building Field Experience and Prmentioning
confidence: 99%
“…Teacher isolation and lack of access to quality professional development highlight the need for building supportive networks among special educators at every level of practice (Boe & Cook, 2006), for it seems impossible to imagine how anyone can practice the pedagogy of inclusion and experience isolation at the same time (Hardman, 2012). Formal and informal networking breaks down isolation and facilitates continuing professional development by creating authentic forums for collaboratively thinking through problems with practice from inside the practice itself (Billingsley, 2004;McLeskey & Waldron, 2000;Smith & Ingersoll, 2004).…”
Section: Developing a Collaborative Culture Of Learningmentioning
confidence: 99%
“…The magnitude of the chronic shortage of fully certified SETs for students aged 6-21 years with disabilities can also be viewed by contrasting the shortage of SETs with that of GETs. Available evidence suggests that, for students in grades K-12, the shortage of fully certified GETs stood at 10.5% (based on 1999/2000 SASS data), whereas the comparable shortage of SETs stood at 13.7% (also based on 1999/2000 SASS data, adjusted upward by 1.1% to account for vacant positions (Boe & Cook, 2006).…”
Section: Trends In Teacher Shortagementioning
confidence: 99%
“…Accordingly, this research capitalizes on the potential of DANS to provide unique insights into the supply, demand, and shortage of SETs. Other recent research with SASS capitalizes on its potential to provide such unique insights about SETs (e.g., Boe & Cook, 2006;Cook & Boe, in press). …”
mentioning
confidence: 99%